Increased risk of idiopathic pulmonary fibrosis in inflammatory bowel disease: A nationwide study. Issue 2 (16th September 2019) - Kim, Jihye; Chun, Jaeyoung; Lee, Changhyun; Han, Kyungdo; Choi, Seungho; Lee, Jooyoung; Soh, Hosim; Choi, Kookhwan; Park, Seona; Kang, Eun Ae; Lee, Hyun Jung; Im, Jong Pil; et al.
Abstract: Background and Aim: The relationship between inflammatory bowel disease (IBD) and idiopathic pulmonary fibrosis (IPF) remains unclear. We evaluated the risk for developing IPF in patients with IBD using a nationwide population‐based study. Methods: Using claims data from the National Health Insurance service in Korea, patients with IBD, including Crohn's disease (CD) and ulcerative colitis (UC), were identified through both the 10th revision of the International Statistical Classification of Diseases and Related Health Problems and rare and intractable disease program codes from January 2010 to December 2013. We compared 38 921 IBD patients with age‐matched and sex‐matched individuals without IBD in a ratio of 1:3. Patients with newly diagnosed IPF were identified by both the 10th revision of the International Statistical Classification of Diseases and Related Health Problems and rare and intractable disease registration codes. Results: During a mean 4.9‐year follow‐up, the incidence of IPF in patients with IBD was 33.21 per 100 000 person‐years. The overall risk of IPF was significantly higher in IBD patients than in non‐IBD controls (hazard ratio [HR], 1.62; 95% confidence interval [CI], 1.20–2.20; P  = 0.003). In patients with CD, the incidence (per 100 000 person‐years) of IPF was 26.04; in controls, the incidence was 9.15 (HR, 2.89; 95% CI, 1.46–5.72; P  = 0.002). The incidence of IPF in patients with UC tended to be higher than in controls (36.66 vs 26.54 per 100 000 person‐years; 95% CI, 0.99–1.99; HR, 1.41; P  = 0.066). The risk of developing IPF in patients with IBD was higher in male patients than in female patients ( P  = 0.093 in CD; P  = 0.147 in UC by interaction analysis). Conclusions: Patients with IBD, especially CD, have an increased risk of developing IPF.